Altman Z Score Method for Predicting Bankruptcy in Kompas 100 Index Companies - Herman Somantri; M. Kohar Mudzakar (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
This study aims to predict bankruptcy in companies indexed in Kompas 100. The research does on 30 sample companies based on a purposive sampling technique for 2019 – 2021. The research does use explanatory and descriptive investigations. The results showed that 18 companies met the healthy category in 2019, 15 in 2020, and 18 in 2021. A gray area category, 2019, 10 companies; 2020, 9 companies. And 2021, 8 companies. For the bankruptcy category, in 2019, 2 companies. In 2020, 6 companies, and in 2021, 4 companies.